A 3D Real‐Scale, Biomimetic, and Biohybrid Model of the Blood‐Brain Barrier Fabricated through Two‐Photon Lithography. Issue 6 (14th December 2017) - Marino, Attilio; Tricinci, Omar; Battaglini, Matteo; Filippeschi, Carlo; Mattoli, Virgilio; Sinibaldi, Edoardo; Ciofani, Gianni
Abstract: The investigation of the crossing of exogenous substances through the blood‐brain barrier (BBB) is object of intensive research in biomedicine, and one of the main obstacles for reliable in vitro evaluations is represented by the difficulties at the base of developing realistic models of the barrier, which could resemble as most accurately as possible the in vivo environment. Here, for the first time, a 1:1 scale, biomimetic, and biohybrid BBB model is proposed. Microtubes inspired to the brain capillaries were fabricated through two‐photon lithography and used as scaffolds for the co‐culturing of endothelial‐like bEnd.3 and U87 glioblastoma cells. The constructs show the maturation of tight junctions, good performances in terms of hindering dextran diffusion through the barrier, and a satisfactory trans‐endothelial electrical resistance. Moreover, a mathematical model is developed, which assists in both the design of the 3D microfluidic chip and its characterization. Overall, these results show the effective formation of a bioinspired cellular barrier based on microtubes reproducing brain microcapillaries to scale. This system will be exploited as a realistic in vitro model for the investigation of BBB crossing of nanomaterials and drugs, envisaging therapeutic and diagnostic applications for several brain pathologies, including brain cancer. Abstract : A 3D, real‐scale, and biomimetic model of the blood‐brain barrier (BBB) is proposed. Taking advantage of the two‐photon lithography technique, an in vitro biohybrid dynamic BBB model is developed and fully characterized, aiming at obtaining a realistic tool for the testing of drug targeting and delivery at the level of the central nervous system.